Differences in mortality and complication rates following revision knee arthroplasty performed for urgent versus elective indications - Abram, SGF; Sabah, SA; Alvand, A; Price, AJ (British Editorial Society of Bone and Joint Surgery, 2021)
Aims: To compare rates of serious adverse events in patients undergoing revision knee arthroplasty with consideration of the indication for revision (urgent versus elective indications), and compare these with primary arthroplasty and re-revision arthroplasty.